The democratic limbo: rule of law, organized crime and paramilitarism in Mexico - Rodríguez Fuentes, Oscar Daniel (2015)
In late 2007, President of Mexico Felipe Calderon Hinojosa implemented a policy of direct confrontation with crime organizations, this decision generated a climate of widespread insecurity and increased high-impact crimes such as arbitrary executions, torture and forced disappearan- ces. In this context of violence some groups of society hired paramilitaries in San Pedro Garza García, Nuevo León and created self-defenses in some cities of Michoacán to protect their rights. This problem exhibited the incapacity of the State to provide public security and the situation of some territories formally under the rule of law but materially controlled by the organized crime.